A brief introduction to China's new Drug Administration Law and its impact on medications for rare diseases - Wang, Yueqiang (Intractable Rare Dis Res, 2019)
The Drug Administration Law of the People's Republic of China (amended in August 2019) is a major piece of legislation governing drug administration in China. This law seeks to improve health legislation; to achieve this, it defines the concepts of fake drugs and inferior drugs and their differences, it emphasizes the regulation of reliability, it standardizes online drug sales, it encourages technological innovation, and it specifies legal liability and punishment through legislative amendments. The Drug Administration Law is characteristic of responsive legislation, and it guarantees a right to health for citizens. The law provides for priority review and approval of new drugs for diseases like rare diseases, it encourages the domestic manufacturing and development of new drugs for rare diseases, and it provides a firm legal basis for medications to treat rare diseases under the Healthy China strategy.